The Impact Of Enterprise Risk Management, Strategic Agility And Quality Of Internal Audit Function On Firm Performance - Lee, Kaih Yeang (2014)
Enterprise risk management or famously known as ERM is an integrated, enterprise-wide approach in assessing events that possibly to impact a firm’s ability to sustain its performance and hinder from achieving its strategic objectives. Due to the complexity of today environment, many firm has shifted from traditional risk management model to enterprise risk management model. At the same time, strategic agility play an important role as it allowed the firm to adapt to the changes quickly and maintain its competitiveness in the business environment. The role of internal audit function is increasing over the years especially with the recommendation from MCCG 2012 for the board to establish an internal audit function in the company.